Comparison of different control loop concepts for direct distance measurement using photonic mixing devices (PMD) - Becker, Dirk; Gulden, Peter; Vossiek, Martin (IEEE Sensors 2002. First IEEE International Conference on Sensors, 2002)
This paper presents two different control loop approaches for distance measurement with photonic mixing devices (PMD). Possible all-analog implementations are pointed out, and measurements with two different loop types using our laboratory PMD system are provided. It is shown that the PI control loop implementation reaches distance accuracy comparable to previous modulation methods, but on the other hand suffers from present offsets of the PMD. For the second method, the steepest descent algorithm, contrary results are obtained. This method is not susceptible to offset variations, but requires a fairly high SNR to converge. Finally the requirements for all-analog closed loop implementation imposed on the next generation of PMD elements are pointed out.
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.compar
Keywords: Electro-optical control loop; PI-controller; PMD distance measurement; Steepest descent

Novel control loop concept for direct distance measurement using photonic mixing devices (PMD) - Becker, Dirk; Gulden, Peter; Vossiek, Martin; Schwarte, R. (OPTO, Internat. Conf. and Exhibition on Optoelectronics, Optical Sensors & Measuring Techniques / Optische Sensorik, Meßtechnik & Elektronik, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.novelc

Novel optical distance sensor based on MSM technology - Gulden, Peter; Becker, Dirk; Vossiek, Martin (IEEE Sensors Journal, 2004)
This paper describes a novel distance-sensor concept based on photodiodes in metal-semiconductor-metal technology (MSM). MSM photodiodes can be operated as electrooptical mixers functioning similar to the so-called photonic mixing device (PMD). This paper employs the correlation techniques previously used with the PMD to the MSM. First, experimental results obtained with the MSM inserted into the authors' standard laboratory setup are provided. Additionally, different configurations well suited for mixer operation of the MSM are pointed out. Throughout this paper, similarities between the PMD and MSM are pointed out, as well as key differences.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.LEH.novelo_4
Keywords: Electrooptical mixer; Metal-semiconductor-metal technology (MSM); Optical intensity-modulation (IM) time-of-flight (TOF) distance measurement; Photonic mixing device (PMD)

Novel optical time-of-flight distance sensor concepts based on MSM and PMD technology - Gulden, Peter; Becker, Dirk; Vossiek, Martin (IRS / GRS, Internat. Radarsymp./German Radar Symp., DGON, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.LEH.novelo

Regenerative Backscatter Transponder Using the Switched Injection-Locked Oscillator Concept - Vossiek, Martin; Schäfer, Tobias; Becker, Dirk (IEEE MTT-S International Microwave Symposium 2008 (IMS 2008), 2008)
In this paper, a new backscatter transponder type is introduced. The developed transponder regenerates a modulated, phase-coherent high-power response/ replica to an interrogating CW radar signal. To create the amplified phasecoherent transponder response, the switched injection locked oscillator (SILO) concept is applied. Compared with a usual passive backscatter transponder - known e.g. from UHF RFID systems - the reading range of a SILO transponder is substantially increased. It is demonstrated that a reading range above 20 m is easily obtained even with a 5.8 GHz, 15 MBit/s system. © 2008 IEEE.
UnivIS-Import:2015-04-16:Pub.2008.tech.IE.LEH.regene
Keywords: Identification; Oscillators; Phase synchronization; Radar; Radio communication; Transponders

Systematic distortions in electro-optical mixers - Gulden, Peter; Becker, Dirk; Vossiek, Martin (IEEE Sensors, 2003)
Electro-optical mixers (EOM) have tremendous potential for application in optical intensity-modulated time-of-flight distance measurement systems. Two different devices, Photonic Mixing Devices (PMD) and Metal-Semiconductor-Metal (MSM) are applied to distance measurement in this paper. The experimental results obtained show the presence of systematic distortions in the output signal of the device, resulting in measurement errors of up to a few centimeters. Careful analysis of the effects leads to the conclusion that illumination dependant non-linear effects take place inside local spots of the semiconductor. Consequently the introduction of a small diffusing plate for beam homogenization in front of the semiconductor drastically reduces the amount of systematic distortions. The distance measurement accuracy is doubled for PMDs, and even tripled for MSMs. Additionally the experimental data provides ties between charge injection mechanisms and the observed spurious signals.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.LEH.system_9
Keywords: Electro-optical mixer; Metal-semiconductor-metal technology (MSM); Photonic-mixing device (PMD); optical intensity-modulation (IM) time-of-flight distance measurement